Assessment of Soil Macrofauna Diversity in Rice Fields and Dry Lands in Panti District, Jember Regency - Laily Mutmainnah; Dimas Verdian Ramdhani; Tri Candra Setiawati (Jurnal Biologi Tropis, 2026)
The variety of soil macrofauna serves as a biological indicator to assess the sustainability of land, especially in farming areas. Soil macrofauna are essential in the nutrient cycle. Macrofauna significantly contribute to the decomposition of soil litter into organic materials. Environmental factors affect the presence of soil macrofauna. Important environmental factors include soil pH, soil temperature, and soil organic carbon content. Differences in these three factors are directly visible in agricultural lands, particularly between rice paddies and drylands. Rice paddies are actively cultivated and flooded agricultural lands. Meanwhile, drylands are agricultural lands that are not actively cultivated. The author intends to explore the variety of soil macrofauna in two distinct land settings. Additionally, the author seeks to assess how variations in land conditions impact the diversity of soil macrofauna. Samples of soil were collected from eight sites located at elevations between 91 and 600 meters above sea level, which included four rice fields and four dryland areas. The study examined several factors, such as soil temperature, soil pH, soil organic matter, and the biodiversity of soil macrofauna. Soil temperature was measured with a soil thermometer. The soil pH was assessed using a pH meter, while soil organic matter was evaluated with the Walkey and Black technique. Observations of soil macrofauna were carried out employing hand sorting and the Berlesse funnel extraction method. The biodiversity of soil macrofauna was determined using the Shannon's Weaver Diversity Index and the Margalef Species Richness Index equations. The findings indicated that soil temperature varied from 23.47 to 27.60 degrees Celsius, soil pH varied from 4.65 to 6.72, and the percentage of soil organic matter ranged from 1.66 to 3.62%. These three elements displayed a negative relationship with the diversity of soil macrofauna, while positively correlating with the richness of soil macrofauna species.